Social anxiety disorder and avoidant personality disorder from an interpersonal perspective. (17th January 2019) - Frandsen, Frederik Weischer; Simonsen, Sebastian; Poulsen, Stig; Sørensen, Per; Lau, Marianne Engelbrecht
Abstract : Objectives: The general objective of this article is to study the unclear and overlapping relationship between social anxiety disorder (SAD) and avoidant personality disorder (AvPD) from an interpersonal perspective. The first specific objective is to compare the disorders with regard to interpersonal problems and general symptom distress. The second specific objective is to examine interpersonal subgroups and pathoplasticity. Design: In a cross‐sectional design, patients from an outpatient psychotherapy clinic diagnosed with social anxiety disorder (SAD, n  = 299), avoidant personality disorder (AvPD, n  = 180), or the comorbid condition of both disorders (AvPD + SAD, n  = 29) were assessed before treatment. Methods: Patients filled out the Inventory of Interpersonal Problems (IIP‐64) and the Symptom Checklist‐Revised (SCL‐R‐90) before treatment. Results and Conclusions: From an interpersonal perspective, the relationship between the diagnostic groups is well described by the severity continuum hypothesis, with similar interpersonal problems related to Nonassertiveness and lower levels of general interpersonal stress in the SAD group compared to the two AvPD groups. However, other differences in severity do not fit the severity continuum hypothesis, as there are no differences in severity on the global severity index, and, moreover, the SAD group has the most severe problems on the SCL‐90 phobic anxiety scale. Interpersonal pathoplasticity is not found in the diagnostic groups or in the full sample. However, three interpersonal subgroups are identified in the full sample, designated as Nonassertive, Friendly‐submissive, and Cold‐submissive. Implications for treatment are discussed. Practitioner points: SAD is characterized by a lower level of interpersonal distress compared to AvPD, but the two disorders are similar in having Nonassertiveness as their general interpersonal problem. Contrary to expectation, SAD and AvPD did not differ in general level of symptom severity, and patients with SAD reported more problems with phobic anxiety than AvPD patients did. When understanding SAD and AvPD as different conceptualizations of the same disorder and analysing all patients together, three distinct interpersonal subgroups emerge, which can be identified as Nonassertive, Friendly‐submissive, and Cold‐submissive.